2022
DOI: 10.2196/34715
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Web-Based Cervical Cancer Survivor’s Story on Parents' Behavior and Willingness to Consider Human Papillomavirus Vaccination for Daughters: Randomized Controlled Trial

Abstract: Background Providing adequate information to parents who have children eligible for human papillomavirus (HPV) vaccination is essential to overcoming vaccine hesitancy in Japan, where the government recommendation has been suspended. However, prior trials assessing the effect of brief educational tools have shown only limited effects on increasing the willingness of parents to vaccinate their daughters. Objective The aim of this trial is to assess the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In Group 2 of our study, 5/120 (4.2%) of the mothers received a vaccination. This rate exceeded the vaccination rate of just 11 (1.2%) out of 909 Japanese mothers in the survey study conducted by Suzuki Y et al It has been reported that one of the main barriers to HPV vaccination in Japan is vaccine hesitancy (8). Social media was the first source in Group 2.…”
Section: Discussionmentioning
confidence: 77%
“…In Group 2 of our study, 5/120 (4.2%) of the mothers received a vaccination. This rate exceeded the vaccination rate of just 11 (1.2%) out of 909 Japanese mothers in the survey study conducted by Suzuki Y et al It has been reported that one of the main barriers to HPV vaccination in Japan is vaccine hesitancy (8). Social media was the first source in Group 2.…”
Section: Discussionmentioning
confidence: 77%
“…A total of 281,280 unique participants were drawn from the 34 included studies 27 , 32 , 34 65 . Twenty-five studies were conducted on parents and/or adolescents (73.5%), while the remaining studies were conducted on healthcare providers.…”
Section: Resultsmentioning
confidence: 99%
“…Their effectiveness in improving vaccination uptake has been well-documented 14 17 , 22 , 25 , 26 . These methods have been rigorously tested through Randomized Clinical Trials (RCTs) 34 43 , and although the results are promising, the implementation of guidelines for health promotion practice presents challenges. Specifically, these challenges arise from the lack of a direct meta-analytic comparison of these five key interventions, complicating the clear assessment of their individual effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lasting impact of health education interventions remains uncertain. For instance, a randomised controlled trail in Japan demonstrated that while a cervical cancer survivor’s story initially increased parents’ willingness to consider HPV vaccination, this effect did not persist and failed to increase vaccination rates among children [ 30 ]. Echoing these findings, a recent systematic review by Escoffery et al emphasised the need to broaden HPV vaccination promotion strategies beyond just educational efforts [ 31 ].…”
Section: Discussionmentioning
confidence: 99%